Brain-derived neurotrophic factor–mediated projection-specific regulation of depressive-like and nociceptive behaviors in the mesolimbic reward circuitry. Issue 1 (January 2018) - Liu, Di; Tang, Qian-Qian; Yin, Cui; Song, Yu; Liu, Yan; Yang, Jun-Xia; Liu, He; Zhang, Yue-Man; Wu, Si-Yin; Song, Ying; Juarez, Barbara; Ding, Hai-Lei; et al.
Abstract : Abstract: Increasing evidence suggests that the mesolimbic reward system plays critical roles in the regulation of depression and nociception; however, its circuitry and cellular mechanisms remain unclear. In this study, we investigated the output-specific regulatory roles of dopaminergic (DA) neurons within the ventral tegmental area (VTA) in depressive-like and nociceptive behaviors in mice subjected to unpredictable chronic mild stress (CMS), using the projection-specific electrophysiological recording, pharmacological manipulation, behavioral test, and molecular biology technologies. We demonstrated that CMS decreased the firing activity in VTA projecting to medial prefrontal cortex (VTA → mPFC), but not in VTA to nucleus accumbens (VTA → NAc), DA neurons. However, both VTA → mPFC and VTA → NAc DA neurons showed increased firing activity in response to morphine perfusion in CMS mice. Behavioral results showed that intra-VTA microinjection of morphine (25.5 ng/0.15 μL) relieved depressive-like behaviors, intriguingly, accompanied by a thermal hyperalgesia. Furthermore, the relief of depressive-like behaviors induced by intra-VTA injection of morphine in CMS mice could be prevented by blocking brain-derived neurotrophic factor (BDNF) signaling and mimicked by the administration of exogenous BDNF in mPFC rather than in NAc shell. Nociceptive responses induced by the activation of VTA DA neurons with morphine in CMS mice could be prevented by blocking BDNF signaling or mimicked by administration of exogenous BDNF in NAc shell, but not in mPFC. These results reveal projection-specific regulatory mechanisms of depression and nociception in the mesolimbic reward circuitry and provide new insights into the neural circuits involved in the processing of depressive and nociceptive information. Abstract : Supplemental Digital Content is Available in the Text.BDNF signaling in the VTA → mPFC and VTA → NAc circuits regulates depressive phenotypes and nociceptive behavior in mice exposed to chronic mild stress.